1991
DOI: 10.3402/polar.v10i2.6751
|View full text |Cite
|
Sign up to set email alerts
|

Copepod grazing and its potential impact on the phytoplankton development in the Barents Sea

Abstract: Compiled data from published and unpublished sources on copepod grazing of the large-sized copepods in the Barents Sea give wide ranges in grazing rates. Approximate average values indicate daily rations of 7-18% for copepodite stages V and VI and considerably higher values for the earliest copepodite stages. It is demonstrated that individual variability in gut fullness of copepods from a given locality is typically very high and not closely related to variable food abundance or depth of occurrence. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…RDA results, derived from cell counts and absorption spectra, demonstrate that cosq values for silicic acid and nitrate concentrations correlate strongly with diatom dominance. Diatom blooms routinely occur as r-strategists in eutrophic spring conditions in the Barents Sea (Båmstedt et al, 1991) and may be found in close association with the marginal ice zone into summer (Strass and Nöthig, 1996), an observation consistent with the geographic and seasonal distribution of diatom biomass across our samples (Figure 3). However, the absence of this pattern in RDA derived from pigments (Figure 4B) requires explanation.…”
Section: Discussionsupporting
confidence: 87%
“…RDA results, derived from cell counts and absorption spectra, demonstrate that cosq values for silicic acid and nitrate concentrations correlate strongly with diatom dominance. Diatom blooms routinely occur as r-strategists in eutrophic spring conditions in the Barents Sea (Båmstedt et al, 1991) and may be found in close association with the marginal ice zone into summer (Strass and Nöthig, 1996), an observation consistent with the geographic and seasonal distribution of diatom biomass across our samples (Figure 3). However, the absence of this pattern in RDA derived from pigments (Figure 4B) requires explanation.…”
Section: Discussionsupporting
confidence: 87%
“…From Sakshaug et al (1994). Based on studies by Båmstedt et al (1991). Dalpadado and Skjoldal (1991), Hassel et al (1991), Haug et al (1991Haug et al ( , 1993, Hopkins and Nilssen (1991), Markussen and Øritsland (1991), Markussen et al (1992), Mehlum and Gabrielsen (1993), Nilssen et al (1992), Ryg and Øritsland (1991), Sakshaug and Slagstad (1992), Schweder et al (1992), Skjoldal (1990, 1992), and Wassmann (1990).…”
Section: Structure and Energetics Of The Pelagic Ecosystemmentioning
confidence: 99%
“…maxima. To maximise grazing and minimise sedimentation (''match''), phytoplankton blooms should not begin too early and they should be of long duration so that the probability of zooplankton stocks encountering phytoplankton blooms is maximised (Sakshaug and Skjoldal, 1989;Båmstedt et al, 1991;Hassel et al, 1991). The late and protracted phytoplankton blooms in the permanently ice-free Atlantic waters may represent good examples of ''match'' whereas the early blooms that arise where sea ice overlies Atlantic water may be textbook examples of mismatch, as are the early spring blooms in Norwegian fjords (Wassmann, 1990).…”
Section: Peak Of Bloommentioning
confidence: 99%